Whole-Body 18FDG-PET in an Arthritis Paraneoplastic Syndrome Revealed an Underlying Hematological Neoplasm - Serge Cammilleri; Marie Caroline Guzian; Jean-Pierre Mattei; Olivier Mundler; Sandrine Guis (Case Reports in Medicine)
We showed the first image of 18FDG-PET, which leads to a diagnosis of lymphoma in an atypical polyarthritis. About 4% of patients with lymphoma or leukemia suffered from rheumatologic paraneoplastic symptoms like arthralgia and about 10% of the patients with rheumatologic or neurologic clinical symptoms develop a solid cancer or hematological neoplasm. 18FDG-PET is an interesting exam to identify an underlying malignancy when a paraneoplastic syndrome is suspected; it can detect the primitive lesion and/or the metastasis lesions. The use of the 18FDG-PET can help to detect earlier hematological neoplasm in cases of paraneoplastic syndrome without a determined cause and to treat more rapidly and specifically the patient.